Bangladesh : Technical Assistance Report-Residential Property Price Indices Mission. (IMF Staff Country Reports; Country Report ;, 2020)
The contents of this report constitute technical advice provided by the staff of the IMF to the authorities of Bangladesh in response to their request for technical assistance. The purpose of the mission was to assist the Bangladesh Bank (BB) in progressing on the compilation of a residential property price index. BB has plans to set up a new data collection system to improve the current existing data starting from July 2020. The new data collection will expand the geographic coverage and the type of dwellings and mostly will increase the current sample resulting in more accurate results. The mission recommended the use of R instead of other software since it allows to perform all the necessary calculations in one script and single software. The mission provided training particularly on the hedonic methods, chain linking and rebasing. The hedonic methods are the most recommended to address the quality changes on the mix of dwellings transacted when following the price of real estate.